PENGARUH PERAWATAN KANGAROO MOTHER CARE TERHADAP SUHU BAYI BBLR DI RUANG NEONATOLOGI RSUD PAMBALAH BATUNG AMUNTAI : The Effect Of Kangaroo Mother Care (Kmc) On The Temperature Of Lbw Infants In The Neonatology Room Of Rsud Pambalah Batung Amuntai - Rakhmadina, Nadya Eka; Yuliana, Fitri; Hasanah, Siti Noor (LPPM - STIKES Pemkab Jombang, 2024)
One method that is able to meet the needs of BBLR babies by providing situations and conditions similar to the mother's womb is KMC Treatment, which is a treatment method by making direct contact between the baby's skin and the mother's skin (skin to skin contact) and placing the baby on the mother's chest. KMC treatment has benefits for the increase in temperature of BBLR babies. The purpose of the study was to determine the effect of KMC treatment on the temperature of BBLR babies in the Neonatology Room of Pambalah Batung Amuntai Hospital. Quantitative research method with quasi-experimental method research design with one group pretest posttest approach. Samples were taken by purposive sampling method and had inclusion and exclusion criteria so that 15 BBLR baby samples were obtained. Data collection using observation sheets. Data were analyzed using the Wilcoxon Sign Rank Test. The results showed that the baby's body temperature before KMC treatment averaged 36,160 and the baby's body temperature after KMC treatment averaged 37,073. Based on the Wilcoxon Sign Rank Test analysis test, there is a significant effect of increase between temperature before and after KMC treatment with p-value (0.001 < 0.05).